How Large Is the Stress from the Common Monetary Policy in the Euro Area? - Dominic Quint (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The ECB's one size monetary policy is unlikely to fit all euro area members, which raises a discussion about how much monetary policy stress this causes at the national level. We measure monetary policy stress as the difference between actual ECB interest rates and Taylor-rule implied optimal rates at the member state level. Optimal rates explicitly take into account the natural rate of interest to capture changes in trend growth. We find that monetary policy stress within the euro area has been steadily decreasing prior to the recent financial crisis. Current stress levels are not only lower today than in the late 1990s, they are also in line with what is commonly observed among U.S. states or pre-euro German L nder.
Keywords: E58; E52; C22; 330